Industry and Revolution: Social and Economic Change in the Orizaba Valley, - Ángela Vergara (H-Industri@)
Gómez-Galvarriato, Aurora, Industry and Revolution: Social and Economic Change in the Orizaba Valley, Mexico, Cambridge y Londres, Harvard University Press, 2013